Mass Transfer Correlations for a Rotating Cylinder Electrode under lsothermal and Controlled Heat Transfer Condition - ALWASH, S.H. (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
Mass transfer correlations for iron rotating cylinder electrode in chloride/sulphate solution, under isothermal andcontrolled heat transfer conditions, were derived. Limiting current density values for the oxygen reduction reaction frompotentiostatic experiments at different bulk temperatures and various turbulent flow rates, under isothermal and heattransfer conditions, were used for such derivation. The corelations were analogous to that obtained by Eisenberg et alland other workers.